Housekeeping Staff Work Strategies In Maintaining Cleanliness And Comfort In 3-Star Hotels In Bali - Putu Agus Murtono; I Putu Sagita Jaya Utama; I Made Ojes Mahardika; I Komang Ardana; Ida Bagus Manuaba (Politeknik Internasional Bali, 2026)
The hotel industry in Bali faces relatively high occupancy rates, requiring continuous operational readiness, particularly in the housekeeping department, which plays a direct role in maintaining cleanliness and guest comfort. Increasing workloads and tight operational schedules demand adaptive work strategies to sustain service quality. This study aims to analyze the work strategies of housekeeping staff in maintaining hotel cleanliness and comfort in Bali. This study employed a qualitative approach through field observations, in-depth interviews with housekeeping staff and supervisors, and analysis of hotel operational documents. Data were analyzed through data reduction, data display, and conclusion drawing, combined with a SWOT analysis. The findings indicate that housekeeping strategies include work rhythm management, flexible task allocation, team coordination, and the use of work experience in handling operational pressures. In practice, staff prioritize room cleaning based on occupancy urgency and apply cross-task assistance to ensure timely room readiness during peak periods. These strategies help maintain consistent cleanliness standards in both guest rooms and public areas. The study implies the need to strengthen housekeeping work systems and internal controls to sustain service quality amid dynamic operational conditions.